Effect of chicken bone hydroxyapatite on inflammation, angiogenesis, and re-epithelialization of post-extraction socket wound healing: an in vivo study - Rafidah Kemala Dewi; Brilla Ayu Kurniawati; Umi Hayyu Nur Saadah; Vincensia Maria Karina; Pingky Krisna Arindra; Tetiana Haniastuti (Majalah Kedokteran Gigi Indonesia, 2026)
Tooth extraction causes tissue discontinuity and triggers wound-healing process. This process begins with inflammatory response, followed by angiogenesis, and re-epithelialization. Hydroxyapatite can accelerate wound healing by increasing growth factors and cytokine secretion by macrophages. Chicken bones are a natural source of hydroxyapatite, containing 85% calcium phosphate. This study aims to determine the effect of chicken-bone hydroxyapatite on inflammatory response, angiogenesis, and re-epithelialization in wound-healing process of post-extraction socket in Wistar rats. Thirty Wistar rats were divided into treatment and control groups, with implantation of chicken bone hydroxyapatite in the treatment group. Extraction was done on left mandibular incisor using excavator and hemostat. The sockets in both groups were then treated with povidone-iodine and sutured. Three rats from each group were killed after 1, 3, 5, 7, 10, and 14 days for histological specimen with hematoxylin-eosin staining. The specimens were observed with light microscope. Data results were then analyzed using a two-way ANOVA and post hoc LSD test (p < 0.05). The results showed significant differences in inflammatory cells, higher blood vessel number, and epithelial thickness among groups and days of observation (p < 0.05). LSD results revealed a significantly lower number of inflammatory cells, different blood vessel numbers, and increased epithelial thickness in treatment group compared to control group. To conclude, the application of chicken bone hydroxyapatite accelerates the inflammatory response, angiogenesis, and re-epithelialization in post-extraction socket healing in Wistar rats.